A Class of Dominance Solvable Common-Value Auctions - Harstad, Ronald M.; Levin, Dan (Review of Economic Studies, 1985)
Dominant strategies seldom exist in non-cooperative games. Moulin's concept of a dominance solvable game generalizes, dominant strategy without dramatic loss in appeal. We consider a class of common-value auctions characterized by the property that the maximum of a collection of informative signals is a sufficient statistic for the entire collection. We demonstrate that this class of second-price auctions is dominance solvable.